Patient’s and Consultant’s Views and Perceptions on Switching from an Originator Biologic to Biosimilar Medication: A Qualitative Study - D. C. Rosembert; M. J. Twigg; D. J. Wright (Pharmacy, 2024)
The aim of this study was to describe the opinions of patients undergoing treatment with originator biologics and medical consultants managing their conditions and identify the barriers and enablers to transitioning from originator biologics to equivalent biosimilars. This study was undertaken prior to biosimilar switching at a large teaching hospital in the United Kingdom. Five gastroenterology, rheumatology, and dermatology consultants were interviewed. Two focus groups were conducted with patients prescribed infliximab (n = 2) and etanercept originators (n = 7). Four main themes emerged, as follows: (1) ‘Benefit to the NHS’; (2) ‘Evidence for efficacy and safety’; (3) ‘Team roles’; and (4) ‘Effective communication during switching’, with sub-themes such as (4a) ‘What patients want to know’ and (4b) ‘How it should be communicated’. Recognition of the ability to save NHS money was an enabler for both patients and consultants, with patients wanting to be reassured that the money saved would be used to benefit other patients. Consultants did not always believe that biosimilars had similar efficacy as the originators or that the manufacturing standards were the same. Effective interventions to address these concerns are required. Offering patients the opportunity to revert back to their originator if necessary was seen as an enabler, as was the provision of readily available mechanisms for reporting suspected adverse events resulting from switching. The role of pharmacy in the process of switching from originator biologics to biosimilars can range from educating consultants regarding the safety and efficacy of biosimilars, explaining the rationale for switching patients, and providing a route for reporting adverse events.